Adsorptive performance of mesoporous silica-modified Bangkok clay as an alternative GCL - Sathawong, Sidthipong; Asadullah; Somsiripan, Thotsaporn; Tohdee, Kanogwan; Jongsomjit, Bunjerd; Jotisankasa, Apiniti; Kamchoom, Viroon; Semmad, Surat (My University, 2026)
This study investigates the adsorption performance and characterisation of mesoporous silica-modified Bangkok clay (BKC) as a geosynthetic clay liner (GCL) for removal of heavy metal in aqueous solution. BKC was modified with mesoporous SBA-15 to create a mesoporous silica-coated clay (5SBS), enhancing its surface area, porosity, and adsorption efficiency. The materials were characterized using Fourier-transform infrared spectroscopy, scanning electron microscopy–energy-dispersive X-ray spectroscopy, X-ray diffraction, Brunauer–Emmett–Teller (BET), and X-ray photoelectron spectroscopy techniques while adsorption experiments of Cu(II), Zn(II), and Cd(II) ions under controlled conditions in ternary systems. The 5SBS composite exhibited superior physicochemical characteristics, including a BET surface area of 67.45 m2/g and well-distributed mesopores. Adsorption kinetics followed a pseudo-second-order model, indicating chemisorption as the dominant mechanism. Equilibrium isotherm data fit best with the Langmuir and Sips models, suggesting monolayer adsorption on homogenous surfaces. The maximum uptake capacities for 5SBS were 31.74, 17.96, and 14.26 mg/g for Cu(II), Zn(II), and Cd(II), respectively, outperforming unmodified BKC and closely matching bentonite. Enhanced thermal stability and minimal pore structure degradation post-adsorption confirmed its suitability for harsh environmental conditions. Metal adsorption has mainly occurred at the surface of the mesoporous silica-modified clay by bonding with surface functional groups. Hydraulic conductivity results further indicate that SBA-15 modification effectively reduces permeability and chemical sensitivity of BKC, maintaining performance comparable to bentonite through stable pore-blocking mechanisms. These findings highlight 5SBS as sustainable alternative to bentonite in GCL, with potential implications for contaminant protection.
Keywords: adsorption; Bangkok clay; chemical properties; heavy metals; surface modification; UN SDG 6: Clean water and sanitation